Framework for Analysis of Factors which Determine Service Quality in a commercial Bank - Rita,; Christopher, Prabu; Ganesan, (Gyan Management Journal, 2010)
The issue of quality management and customer satisfaction in banking services becomes major concern and :-: • .;n considerable attention in the recent past. The outstanding progress and establishment of banking ,;es help the banks to retain its existing customers and also targets the new customers. Delays and -1bility in service often undermine the delivery of customer service. At this juncture evaluating the bank's  rmance is extremely important. This can be evaluated through a set of considerable factors which the strengths and weaknesses. To identify these critical factors, it is necessary to assess the service :·.; ·:cy gap between customers' expectations and services offered. Through principal component analysis two -; ::.:,rs are extracted such as, must be customer requirements and Fairness in treating customers. In this -- : :::,er, the quality of service is measured through SERVQUAL methodology is framed for continual: ·ovement of banking service. This paper gives valuable insight and constructive plans to enhance customer :faction.
Keywords: Commercial Bank (CB); Service Quality, SERVQUAL